PENGARUH PROFITABILITAS, LIKUIDITAS, PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL DENGAN SUKU BUNGA BI SEBAGAI VARIABEL MODERASI - Tania Alvianita Pramudya; Jonnardi; M. F. Djeny Indrajati (Jurnal Kontemporer Akuntansi, 2024)
During the covid-19 pandemic, companies experienced a decline in sales and even experienced losses. This hasresulted in many countries and companies surviving and financing their people with debt. There are factors thataffect the company's capital structure, such as profitability, liquidity, sales growth, and BI interest rates. To test theeffect, a sample of non-financial sector companies listed on the Indonesia Stock Exchange (BEI) was used usingmultiple regression analysis. And the result is that all variables except sales growth have a significant effect oncapital structure.